Error of single-jet water meter indications caused by configuration of frequency converter controled local pumping stations – case study - Koral, Wojciech (Instal, 2020)
The paper shows results of research on configuration error of local pumping stations supplying multi-family buildings: pulse of pressure and failure of indication of the main (single-jet) water meters.
Keywords: water balance; single-jet water meter; water-meter errors